Antagonistic activity of Trichoderma harzianum against Aspergillus parasiticus and Mucor circinelloides in corn plant (Zea mays L.) - Susiana Purwantisari; Farah Arhusy Nurbayani; Marista Fikri Irsya Safina; Miftahul Choiriyah (PLANTA TROPIKA, 2025)
Aspergillus parasiticus, the causative agent of Aspergillus cob rot, and Mucor circinelloides, which causes Mucor stem rot, are types of pathogenic fungi that have the potential to reduce the quality of corn (Zea mays L) harvests. An effective and environmentally friendly approach to control these pathogens is to use biological agents, such as Trichoderma harzianum. This study aims to evaluate the inhibitory potential of T. harzianum against A. Parasiticus and M. circinelloides using antagonism tests with dual culture methods in vitro. The parameters used in this study were measurements of the percentage of the inhibition rate of the biological agent T. harzianum against pathogenic fungi. The results of the antagonism test showed that the biological agent T. harzianum had moderate inhibition against A. parasiticus and M. circinelloides with the percentage of each inhibition during the five days incubation period are 32.5% and 42.38%. This indicates that T. harzianum has the potential as a biological agent in controlling A. parasiticus and M. circinelloides in corn plants.